EKSISTENSI FUNGSI PENGAWASAN DPRD TERHADAP PENGELOLAAN APBD KOTA PAREPARE - aman, Badruzz; Anwar, Alfiansyah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2019)
The data in this study are primary data obtained from questionnaires distributed directly to respondents. Data collected from only 28 respondents consisted of members of the DPRD, Regional Government and community leaders in the City of Parepare.The results of this study indicate that, first, the functioning of the DPRD's oversight for the 2014 period. 2019 on the management of the 2016 APBD in the City of Parepare can be categorized as efficient. Because of the educational support and knowledge of the members of the Parepare City DPRD. From the level of experience and background of the organization Members of the Parepare City DPRD have provided support because the average member of the DPRD City of Parepare is experienced in organizing. Judging from the public response to the implementation of the oversight function of DPRD members on the management of the Regional Budget in Paepare City, the response was quite good, because in general, the level of public trust in Parepare City DPRD members was relatively high.